Can PIMS-TS lead to a facial nerve palsy?. Issue 6 (14th June 2021) - Hookham, Lauren; Teoh, Penelope; Stern, William; Goodman, Anna L
Abstract : Paediatric inflammatory multisystem syndrome—temporally associated with SARS-CoV-2 (PIMS-TS) is a recently described syndrome. We describe the case of a 17-year-old man presenting with a recent illness consistent with COVID-19 who presented with fever, chest pain and anterior uveitis. He was treated with aspirin, pulsed methylprednisolone and tocilizumab followed by oral steroids. On day 16 from initial presentation, he developed a facial nerve palsy. He was managed with ongoing steroids and the addition of valaciclovir. PIMS-TS is an under-recognised condition among adult physicians and may not be well known in adult neurology. It is important for adult physicians and neurologists to be aware of PIMS-TS and its possible sequelae.